The induction of liver growth by peroxisome proliferators - Al Kholaifi, Abdullah (2008)
Peroxisome Proliferators (PPs) are a class of chemicals that cause a programme of augmentative liver growth, however, the mechanism which regulates the induction of hepatic DNA synthesis as a result of exposure to peroxisome proliferators is currently uncharacterized.